Industry-oriented method for the aqueous phase oxidation of crude 5-hydroxymethyl furfural (HMF) to 2,5-furandicarboxylic acid (FDCA) - Lokhande, Priya; Sonone, Kalyani; Dhepe, Paresh L. (New Journal of Chemistry, 2023)
Valorization of cellulose, hemicellulose, and lignin into value-added industrially relevant chemicals is important to achieve sustainability goals that various governments and industries have set. In view of this, the oxidative synthesis of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethyl furfural (HMF) as an analogous compound to terephthalic acid in the synthesis of PEF is interesting to researchers. Though advancements in the oxidation of HMF have been made, the efficient synthesis of HMF, its storage, and isolation are great challenges due to its instability under normal conditions. While purified HMF can be used to synthesize FDCA, it is imperative to use crude HMF for the synthesis of FDCA since several techno-economical studies reveal that the purification of HMF is the most cost-intensive step. Herein, we demonstrate the oxidation of crude HMF, synthesized in the laboratory to FDCA, using nonprecious-based mixed metal oxides in the aqueous medium in the presence of oxygen/air. Among various catalysts, Cu-Mn catalyst at 120 & DEG;C within 8 h in the presence of oxygen (10 bar) could yield 90% FDCA. This activity was comparable with that of the commercially available and well-studied Ru/C (5 wt%) catalyst (93% yield). In addition, the role of HMF purity, air as an oxidant, and the influence of temperature, pressure, and time is systematically studied. It is also demonstrated that FDCA formation proceeds via HMFCA and FFCA formation. The isolation of FDCA and its purity (>99%) is corroborated with various techniques such as NMR, IR, and HRMS.